2013
DOI: 10.1590/s0100-29452013000100016
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento dos frutos de lulo (Solanum quitoense LAM), em Viçosa-MG

Abstract: RESUMO -O lulo é um fruto tropical e exótico, originário dos Andes, tem cor laranja quando maduro, e é uma baga globosa, assemelha-se a um tomate, o epicarpo é grosso e coriáceo, sua polpa é verde-clara, pegajosa, ácida e suculenta, contendo muitas sementes. Objetivou-se acompanhar as características físicas, químicas e fisiológicas ocorridas durante o desenvolvimento do fruto de lulo, da antese ao amadurecimento completo, em Viçosa-MG. Os frutos apresentaram um padrão de crescimento sigmoidal simples em respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
0
5
0
3
Order By: Relevance
“…The MI is inversely proportional to the titratable acidity, which is related to the fact that the organic acids are used during maturation process, either through respiration or transformation into sugars (Lombardi;Moraes;Camelatto, 2000;Matarazzo et al, 2013). In a research conducted with tomatoes, Zhu et al (2017) observed lower fruit maturation rates when plants were treated with 1 mg L -1 of Se in the form of selenite.…”
Section: Physical-chemical Characteristics and Carotenoid Contents Inmentioning
confidence: 99%
“…The MI is inversely proportional to the titratable acidity, which is related to the fact that the organic acids are used during maturation process, either through respiration or transformation into sugars (Lombardi;Moraes;Camelatto, 2000;Matarazzo et al, 2013). In a research conducted with tomatoes, Zhu et al (2017) observed lower fruit maturation rates when plants were treated with 1 mg L -1 of Se in the form of selenite.…”
Section: Physical-chemical Characteristics and Carotenoid Contents Inmentioning
confidence: 99%
“…5); de igual manera, este incremento en los ácidos orgá-nicos durante la maduración, podrían dar explicación sobre la dinámica de la ATT para las dos variedades. De otra parte, Yahia et al (2001) sugieren que la baja actividad enzimática del ácido ascórbicooxidasa en los frutos, permite que las concentraciones de vitamina C sean mayores, ya que esta es la responsable de la degradación oxidativa del ácido ascórbico en tejidos vegetales durante el proceso de maduración (Matarazzo et al, 2013), lo que explica lo encontrado en esta investigación.…”
Section: Acidez Total Titulableunclassified
“…Geographically, the experimental area is located at a latitude of 20°45'20'' south and a longitude of 42°52'40'' west, with an altitude of 650 m.a.s.l., with an average annual temperature of 19 °C. According to Köppen's classification, the weather is Cwa-type, mesothermal, with rainy summers and cold, dry winters (Matarazzo et al 2013). …”
Section: Study Areamentioning
confidence: 99%